2006
DOI: 10.1007/s00127-006-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of pathways to care among hospitalized urban African American first-episode schizophrenia-spectrum patients

Abstract: The findings indicate that pathways to care in this population are highly variable, and there is a need for additional research to better understand the nature and determinants of these pathways. Such investigations may provide insights into service enhancements that can promote early detection and intervention, thus improving illness outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 38 publications
2
50
2
Order By: Relevance
“…Another study from the current setting revealed that urban African Americans have highly variable pathways to care [10]. These findings indicate various barriers to care which impact DUP, including factors within health services that are difficult to navigate.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Another study from the current setting revealed that urban African Americans have highly variable pathways to care [10]. These findings indicate various barriers to care which impact DUP, including factors within health services that are difficult to navigate.…”
Section: Discussionmentioning
confidence: 80%
“…Pathways to care likely differ for various populations [9][10][11][12][13]. Given the importance of discovering determinants of DUP, some of which evolve during pathways to care, and in light of the fact that families commonly initiate evaluation and treatment, this study explored narrative accounts of family members who had been actively involved in initial treatment-seeking for their loved ones with first-episode psychosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substance use disorders modules were administered to diagnose substance use disorders. As reported previously (Compton et al, 2006; Compton et al, 2008b) DUP was defined as the number of weeks from the onset of positive psychotic symptoms until first hospital admission, and was measured in a systematic manner using the Symptom Onset in Schizophrenia (SOS; Perkins et al, 2000) inventory, in addition to select items from the semi-structured Course of Onset and Relapse Schedule / Topography of Psychotic Episode (CORS/TOPE; Norman and Malla, 2002) interview. Onset of positive symptoms was operationalized as the date on which hallucinations or delusions met the threshold for a PANSS (Kay et al, 1987) score of ≥3, and systematic methods were used to resolve difficulties in obtaining exact dates for the onset of psychotic symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Violent behavior, male gender, experiencing more severe psychosocial stressors, and spending more time in the emergency setting have been found to characterize those patients referred by law enforcement officers to PES compared to other modes of referral, such as referral by health care providers, selfreferral, and other referral sources (Redondo and Currier 2003;Way et al 1993). Furthermore, race/ethnicity and its socioeconomic correlates may play a role in pathways to care, as exemplified by research indicating high rates of police involvement and police referral to psychiatric services for ethnic minorities with psychotic disorders (Bhugra et al 2000;Burnett et al 1999;Commander et al 1999;Compton et al 2006a, Fisher et al 2004Garety and Rigg 2001;Jarvis et al 2005;Morgan et al 2004Morgan et al , 2005a. In recognition of the role that police officers often assume in psychiatric referral and mental health crisis situations, as well as the widespread problem of criminalization of people with mental illnesses, many law enforcement agencies have implemented crisis intervention programs in collaboration with community partners.…”
Section: Introductionmentioning
confidence: 98%